Gobierno, legitimidad y movilización: aspectos de la vida electoral en tiempos insurgentes - Ducey, Michael Thomas (El Colegio de México, A.C., 2019)
Starting from Virginia Guedea’s valuable observations on the insurgent elections called by José María Morelos in 1813, this article, which is based on information found in the General Archive of the Nation and printed collections of primary sources, examines the function of elections in rural areas of the country that were controlled by rebel forces. Rather than discussing the national political issues associated with the Congress of Chilpancingo, it centers on the electoral experience in towns located in insurgent territory. Elections allowed the middle and low-ranking commanders of the rebellion to strengthen their position vis-à-vis local society, making their authority evident in the eyes of the population and taking advantage of events to establish their legitimacy as governors. They also functioned as public events for demonstrating affiliation with the movement and an opportunity to mobilize locals to support them. Besides the question of social mobilization, this article explores the language of the parties involved and the ritualistic aspects of the elections to examine the mentality of the insurgents. In this way, we can better understand how they conceived the role of corporations in the project of constructing a national representative, republican government on the basis of the country’s communities. The article concludes that the revolutionaries organically took advantage of colonial traditions rooted in the Indian Republics to create an innovative vision of the relationship between society and the government.